Comparative Analysis Cryptocurrency Of Bitcoin, Stock, and Gold Return and Risks as Alternative Investments (2015-2020) - Aldhi Maldini (Universitas Negeri Padang, 2022)
Investment requires an objective picture to investors related to the returns to be obtained and the risks to be faced. Therefore, this study aims to determine whether there are differences in return, risk, sharpe, treynor and jensen from bitcoin investment instruments, lq45 shares and gold. Then this research also aims to provide investment strategies to investors to invest in bitcoin, lq45 stocks and gold. This research is a quantitative research using Kruskal Wallis statistical test. The data used is the monthly closing price of bitcoin, lq45 shares and gold from January 2015-December 2020 obtained from investing.com. At the testing stage, it was found that: (1) there was no significant difference between the returns of Bitcoin, LQ45 shares, and gold, (2) there was a significant difference between the risk of Bitcoin, LQ45 shares, and gold, (3) To invest in Bitcoin, the strategy that is suitable for investors is a passive strategy, namely the Buy you Hold strategy, (4) Investing in LQ45 Stocks a suitable strategy for investors is an active strategy, namely the price momentum strategy, (5) While investing in gold, the strategy that is suitable for investors is an active strategy, namely the Dollar Cost Averaging.